PENCEGAHAN DAN PENANGANAN STUNTING MELALUI KEGIATAN PENYULUHAN, PEMBERIAN MAKANAN TAMBAHAN (PMT), DAN PEMBERDAYAAN USAHA KELUARGA DI DESA CINTARATU KECAMATAN PARIGI KABUPATEN PANGANDARAN - Sukoco, Iwan; Hermanto, Bambang; Gemiharto, Ilham; Fordian, Dian (Universitas Padjadjaran, 2025)
The issue of stunting is a global concern that requires serious attention from all stakeholders. In 2024, the Government of the Republic of Indonesia aims to reduce the stunting rate to 14%. Based on this objective, the Pangandaran Regency government, particularly in Cintaratu Village, has implemented various activities to prevent and address stunting. The method used in this PKM activity is counseling to optimize the management of small, healthy, and prosperous families. Stunting prevention and intervention ef orts have been carried out through counseling, the provision of supplementary food (PMT), and the empowerment of family businesses. These activities have been implemented according to plan and are running ef ectively. Additionally, health services through Posyandu (integrated health post) are operating regularly and ef iciently. Field research results indicate that there are no toddlers identified as stunted in Cintaratu Village, Parigi District, Pangandaran Regency.Masalah stunting merupakan permasalahan dunia yang perlu perhatian serius dari semua stakeholder. Pemerintah Republik Indonesia di tahun 2024 ini mencanangkan penururan stunting sampai 14 %. Berdasarkan alasan tersebut bagaimana pemerintah Kabupaten Pangandaran, khususnya di Desa Cintaratu melakukan kegiatan pencegahan dan penanganan stunting. Metode yang digunakan pada kegiatan PKM ini, berupa penyuluhan optimalisasi manajemen keluarga kecil, sehat dan sejahtera. Kegiatan pencegahan dan penanganan stunting melalui penyuluhan, pemberian makanan tambahan (PMT), dan pemberdayaan usaha keluarga sudah dilaksanakan sesuai rencana dan berjalan dengan baik, layanan kesehatan melalui posyandu sudah berjalan baik dan teratur. Hasil penelitian lapangan tidak ada balita terindikasi stunting di Desa Cintaratu Kecamatan Parigi Kabupaten Pangandaran.